Estudos fotofísicos e fotodinâmicos da clorofila a e derivados formulados em micelas poliméricas e lipossomos - Gerola, Adriana Passarella (2013)
The combination of a photosensitizer (PS), light and oxygen is the base of the photodynamic therapy (PDT) and photodynamic inactivation of micro-organisms (PDI). Chlorophylls compounds present interesting characteristics which can be used as PS in PDT. The chlorophyll (Mg-Chl) and derivatives: zinc chlorophyll (Zn-Chl), pheophytin (Pheo), pheophorbide (Pheid) and zinc chlorophyllide (Zn-Chld) were studied. The chlorophylls were formulated in polymeric micelles (F-127 and P-123) and liposomes (DPPC). The formulated micellar systems were analyzed for temporal and thermal stability. In addition, all the samples were analyzed concerning the PS location in carrier systems, surface charge density, and photophysical properties such as fluorescence (FF) and singlet oxygen quantum yields (FD), photostability and application against microorganisms. The PS have been incorporated into polymeric micelles and liposome in the monomeric form by the solid dispersion method. The formulation kept the spectroscopic and photophysical properties (fluorescence and singlet oxygen quantum yields) of chlorophylls, which allowed the application in photodynamic assays. The thermal stability of micellar formulation was evaluated by electronic absorption spectroscopy and fluorescence emission, simultaneously to the analysis of resonant light scattering. The thermal stability of these formulations was dependent on specific interactions between the PS and the copolymer. At low temperatures below the critical micelle temperature, there was a change in the properties of the micellar microenvironment such as increased viscosity and decreased polarity. These have caused changes in the spectral profiles of chlorophylls, mainly in the fluorescence emission intensities. Analyses of the surface charge density of carrier systems were evaluated by the zeta potential. Polymeric micelles exhibited a negative surface charge density, whereas liposomes showed positive surface potential. This indicates that the liposomes are carrier systems more advantageous for application to membranes (negative charge). The incorporation of PS affected the potential surface of the carrier systems, approaching to zero. This decreases the stability of suspensions and leads to agglomeration of the particles. The location of chlorophyll in carrier systems was evaluated by fluorescence quenching studies using iodide as quencher, and by variation of the absorption and emission energy. In micellar systems, the chlorophylls with the phytyl chain (Mg-Chl, Zn-Chl and Pheo) were located in the hydrophobic core of the micelle and the phorbides derivatives (Pheid and Zn-Chld) in the outer layer (hydrophilic). In liposomes, the chlorophylls with phytyl chain showed the chlorin ring located near the polar head and the phytyl chain inserted in lipid bilayer. In addition, the phorbides derivatives were incorporated into the outer layer of the liposome, near to the polar region of phospholipid. Pheo and Pheid remained stable under light, while metallo-chlorophylls (with Zn2+ and Mg2+) undergo photobleaching. The order of degradation rate of chlorophyll was Mg-Chl> Zn-Chld> Zn-Chl for all systems studied. The same order was obtained in ethanol. The photobleaching process of chlorophyll was dependent on the environment in which the molecules were incorporated. The degradation rate followed the order: DPPC> F-127> P-123. Chlorophyll derivatives led to the photodynamic eradication of Staphylococcus aureus. The formulation of chlorophylls in DPPC enhanced the photodynamic action, which was dependent of photobleaching processes, location, FD and PS uptake by microbial cell. Additionally, ultrastructural changes analyzed by transmission electron microscopy showed that the main targets of photodynamic action on S. aureus cells are the cytoplasmic membrane and the nucleic acids. Analysis of the physicochemical properties of formulations together with results of photodynamic inactivation showed that chlorophyll derivatives are potential PS for PDI mainly the phorbides derivatives (Pheid and Zn-Chld) in liposomes